2020
DOI: 10.1007/s40789-020-00327-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of fracture mechanism for surrounding rock hole based on water-filled blasting

Abstract: The principles of fracture development during underwater blasting are examined based on explosion and impact dynamics, fluid dynamics, fracture dynamics, and field testing. The research reveals that the fracturing of the surrounding rock during underwater blasting is due to the combined action of shock and stress waves for the initial rock breakage and subsequent water expansion. The fracture development model for the surrounding rock of a drilling hole during underwater blasting is established. The rock fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Before running the LS-DYNA 3D program, five elements are designated as observation points to facilitate analyzing and processing the numerical results [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. As shown in Figure 3, points H69786, H68778, H68787, H62503, and H61486 are selected at the lower part of the centerline of two blast holes, which are signed as A, B, C, D, and E, respectively.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…Before running the LS-DYNA 3D program, five elements are designated as observation points to facilitate analyzing and processing the numerical results [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. As shown in Figure 3, points H69786, H68778, H68787, H62503, and H61486 are selected at the lower part of the centerline of two blast holes, which are signed as A, B, C, D, and E, respectively.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…Fracturing pumps, fracturing pipes, grooving drill bits, and other equipment are used to fracture roofs in the process of hydraulic fracturing to reduce the integrity of the roofs and achieve the goal of ground pressure control (Lu et al 2015;Yu and Duan 2014). By using liquid explosive, confined waterfilled blasting technology can not only realize safe blasting but also improve the blasting ability to the maximum extent to reduce the breaking strength of hard roofs Wang et al 2020). However, constrained by the equipment, drilling hole length, and other conditions, the above technologies are limited to underground operation only, and the control range is within 50 m, which cannot fracture hard roofs at high level.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [8] detailed the state of the art in research on top coal drawing mechanisms in Long wall top coal caving (LTCC) by examining the relevant literature over the past two decades. Wang et al [9] revealed that the fracturing of the surrounding rock during underwater blasting is due to the combined action of shock and stress waves for the initial rock breakage and subsequent water expansion. Song et al [10] analyzed the modulus degradation of concrete subjected to multilevel compressive cyclic loading.…”
Section: Introductionmentioning
confidence: 99%